Embedding 21st century soft skills in Islamic higher education - Abd Aziz Rekan; Nurhasfirah Rosin; Muhamad Nasir Mohamad Salleh; Asyraf Isyraqi Jamil; Hafeezur Rahman Awel; Miftachul Huda; Muhammad Baiqun Isbahi (Universitas KH Abdul Chalim Mojokerto, 2025)
Soft skills such as communication, leadership, teamwork, problem solving and entrepreneurship are increasingly recognised as essential for preparing graduates to thrive in today’s complex and competitive global workforce. This study investigates the integration of these 21st-century soft skills within Malaysian higher education, with a specific focus on the Special Arabic Language Program (SALP) at a public institution. Using a qualitative case study design, data were collected through semi-structured interviews with SALP alumni and supported by document analysis related to the programme. The findings reveal that both academic and co-curricular components of the SALP have played a significant role in developing students’ soft skills. These experiences have fostered competencies in communication, leadership, social engagement and entrepreneurship, all nurtured within a framework grounded in Islamic values.